Government policy as a key moderator to contractors’ risk attitudes among Malaysian construction companies - Taofeeq, D. M.; Adeleke, A. Q.; Lee, Chia Kuang (Emerald Publishing Limited, 2020)
Purpose: The main parties in construction projects are the engineers, clients, architects, contractors, material suppliers, and consultants such as the project managers. They play the most important roles in implementing construction projects, and their activities have a significant impact on their risk attitudes during the execution of projects. Because each participant has their particular interests, by proprietary information, each participant is driven to achieve maximum benefit, which can result in improper behaviour concerning each other. The risk in this situation is that there would be a moral hazard and adverse selection based on information asymmetry among principal construction participants especially contractors; this outcome is called risk attitudes. Behaviour is affected by various risk factors and the successful implementation of construction projects depends on effective management of the key risk factors part of which is a personal factor. The purpose of this paper is to identify the critical factors affecting contractors’ risk attitudes among Malaysian construction companies with the moderating role of government policy. Organizational control theory and expected utility theory were used to develop the theoretical framework. The study investigated G7 contractors in the Malaysian construction industry. Data were collected through the use of a questionnaire. Design/methodology/approach: The research analysis was based on structural equation modelling (SEM), and the research model was ascertained through the Smart PLS 3.0 software (Ringle et al., 2012). Partial least square-SEM is an appropriate analysis that was used to assess the results in the current research because its algorithm permits the unrestricted computation of cause-effect relationship models that use both reflective and formative measurement models. This study uses the quantitative method to identify the individual factors influencing contractors’ risk attitude and the moderating role of government policy among construction companies in Malaysia. This study also focussed on the G7 contractors operating in the Malaysia construction industry that specializes in building, bridge and road construction projects. The duration of the data collection was between two and three weeks. The questionnaire was prepared both in Malay and English languages to allow the respondents to respond most conveniently. Before the copies of the questionnaire were distributed, the selected contractors’ committees were duly informed about the details of the survey procedures. The adopted Likert scale was originally a five-point scale that ranges from “very low” to “very high” with “low or high” in between. Findings: The result of this study moderately supports the hypothesized relationships proposed in the theoretical model. In particular, the results recommended that personal factors that affect risk attitudes (working experience, emotional intelligence, professional competence and physical health) have a significant relation with contractors’ risk attitudes in the construction companies in Malaysia. Also, it has been found that government policy (rules and regulations) are important determinants of risk attitudes. Research limitations/implications: The study focussed on individual factors affecting contractors’ risk attitudes in the construction company’s in Malaysia. Therefore, the dimensions of factors affecting risk attitudes can be used in another aspect of construction projects such as management factors, economic factors and technical factors. Therefore, further research might investigate other grades of Malaysian construction companies apart from Grade 7 contractors to know if there is a similarity in the results; other grades of the contractors might have potential positive contributions to the construction industry as well. Practical implications: With consider to the practical, the current research findings have several contributions for the contractors and project managers. The research results demonstrate that government policy plays an important role in the construction industry and organizational support will also help contractors to control their attitudes in working place. Individual factor has a direct relationship with contractor risk attitudes (CRA), project managers must ensure that the government policy has an impact in all their workers and offered is competitive, fair and by their employees’ contribution. Apart from that managers should also focus on organizational goals especially in managing professional and skilled contractors in the companies. Employees who perceived their employers as uncaring or not supporting their needs and well-being may not be happy working with the organization and the tendency for them to change their attitudes towards risk will be high. Social implications: This study also contributes knowledge by lending empirical support to the organizational control theory and expected utility theory system’s effect on CRA and confirming that changing one individual attitude will change the whole equilibrium. This is useful to aid in further synthesis of organizational control theory and expected utility theory in construction companies. Originality/value: This study is the first attempt at evaluating the direct and moderating effect relationships among individual factor affecting risk attitudes, government policy and CRA in Malaysian construction companies. These findings also prop up the applicability of the organizational control theory and expected utility theory within the context of construction companies in Malaysia. Also, this study contributed to the literature on psychology by subjective (psychological) measures of individuals’ behaviour and decisions. In the CRA literature, there has been much discussion on personal characteristics to understand behaviours such as attitudes of a contractor towards risk and morals.